2022
DOI: 10.1111/jpi.12829
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin improves cardiac remodeling and brain–heart sympathetic hyperactivation aggravated by light disruption after myocardial infarction

Abstract: Light in the external environment might affect cardiovascular function. The light disruption seems to be related to changes in cardiovascular physiological functions, and disturbing light may be a risk factor for cardiovascular diseases. Prior studies have found that light disruption after myocardial infarction (MI) exacerbates cardiac remodeling, and the brain‐heart sympathetic nervous system may be one of the key mechanisms. However, how to improve light‐disrupted cardiac remodeling remains unclear. Melatoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 53 publications
2
8
0
Order By: Relevance
“…In addition to β-NMN, melatonin, another renowned circadian regulator that has been considered the primary pharmacologic therapy for circadian disruption-associated symptoms, 45,46 can also offer therapeutic benefits in mitigating the adverse effects of light disruption on kidney function. 32,33,47 Although our findings align with the protective effects of melatonin and β-NMN observed in various circadian disruptionrelated pathological processes, 23,35,48,49 following studies are still necessary to further elucidate their detailed renal-protective mechanisms.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In addition to β-NMN, melatonin, another renowned circadian regulator that has been considered the primary pharmacologic therapy for circadian disruption-associated symptoms, 45,46 can also offer therapeutic benefits in mitigating the adverse effects of light disruption on kidney function. 32,33,47 Although our findings align with the protective effects of melatonin and β-NMN observed in various circadian disruptionrelated pathological processes, 23,35,48,49 following studies are still necessary to further elucidate their detailed renal-protective mechanisms.…”
Section: Discussionsupporting
confidence: 78%
“…Mechanistically, several studies have suggested a close association between circadian disruption and enhanced release of adrenal catecholamines and RAAS activation 35–38 . In our investigation, we examined the serum levels of several hormones, including epinephrine, noradrenaline, angiotensin II, aldosterone, and corticosterone.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The link between antioxidants and cardiovascular physiology has a rather long history, but only recently has more space been given to the clinical meaning and relevance that this relationship may have. Specifically, among the antioxidants, special attention was given to melatonin, according to its antihypertensive, antioxidant, and vasoprotective effects [40,41]. The main point was the possibility of acting on the morphostructural alterations induced by EH, improving in the short and long term the expectation and quality of life of the patients involved [5,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…The elevated damage seems to be a result of stimulation of the brain-heart sympathetic nervous system axis, which exaggerates the size of the infarct area with the development of fibrosis. Supplementation with melatonin overcame much of the cardiac injury by reversing cardiac remodeling, probably due to the suppression of the brain-heart sympathetic hyperactivation [70]. In a rat model of metabolic syndrome, orally administered melatonin beneficially modulated the electrical activity of the heart (normalizing the QT interval) as well as the left ventricular expression of KCNK and KVNH2 genes, both of which encode cardiac potassium ion channels [71].…”
Section: Melatonin and Cardiac Fibrosismentioning
confidence: 99%